Differential Induction Pattern Towards Classically Activated Macrophages in Response to an Immunomodulatory Extract from Pleurotus ostreatus Mycelium - Gabriel Llauradó Maury; Humberto J. Morris-Quevedo; Annick Heykers; Ellen Lanckacker; Davie Cappoen; Peter Delputte; Wim Vanden Berghe; Zelene Salgueiro; Paul Cos (Journal of Fungi, 2021)
Pleurotus ostreatus mushroom preparations have been investigated because of their ability to modulate the immune function. However, there is still no consensus regarding the activation and polarizing effect on macrophages by Pleurotus-derived bioproducts. This study examined the immune-activating effect of a mycelium-derived P. ostreatus aqueous extract (HW-Pm) on macrophage functions, by means of the determination of nitric oxide (NO) production, the mRNA expression of inducible nitric oxide synthase (iNOS), Arginase-1 and FIZZ and the cytokine levels. The phagocytic activity and the activation of NF-κB in U937 reporter cells were also investigated. No cytotoxicity was observed in macrophages treated with HW-Pm (IC50 > 1024 μg/mL) by the resazurin test. HW-Pm induced high levels of NO production and iNOS expression in macrophages. In contrast, HW-Pm did not induce Arginase-1 and FIZZ mRNA expressions. The mushroom extract increased TNF-α and IL-6 production and the phagocytic function in murine macrophages. It also stimulated the activation of the NF-κB promoter. The P. ostreatus mycelium extract has a potential application as a natural immune-enhancing agent, by targeting macrophage activation towards the classically activated subset and stimulating macrophage-mediated innate immune responses.